Molecular characterization and pathogenicity of stagonosporopsis cucurbitacearum causing gummy stem blight disease of watermelon (Citrullus lanatus L.) in Malaysia - Abdul Aziz Waziri,; Dzarifah Zulperi,; Siti Izera Ismail, (Universiti Kebangsaan Malaysia, 2023)
Watermelon (Citrullus lanatus L.) is a popular fruit crop with high economic value and widely grown in Malaysia. In January 2020, gummy stem blight (GSB) has become a threat for production of watermelon in Malaysia particularly in warm and humid climates, but the causative agent of GSB infecting watermelon is unknown. This disease decreases the fresh fruit marketability. Watermelon plants cultivar Red Rocky showing varied degree (40-90%) of suspected GSB, were collected from two main watermelon growing areas in Malaysia. Initial symptoms appeared as marginal brown necrotic lesions on leaves, while on the stems showed water-soaked, necrotic lesions and exuded reddish-brown gummy exudate on the stems. A total of ten isolates were isolated from lesions on leaves and stems of watermelon plants affected by GSB. All ten fungal isolates were identified as Stagonosporopsis cucurbitacearum on the basis of morphological characteristics and phylogenetic analysis of combined sequences of the internal transcribed spacer (ITS) and β-tubulin regions. All isolates were proven to be pathogenic when inoculated on the leaves and stems of the watermelon plant and the the fungal isolates were consistently reisolated from the diseased watermelon plants confirming Koch’s postulates. Pathogenicity tests indicated that there were significant differences in virulence among the S. cucurbitacearum when inoculated on the leaves and stems of the watermelon plant. Understanding the etiology of the pathogen will help in disease management of gummy stem blight disease in Malaysia.